2016
DOI: 10.1007/978-3-319-49583-5_48
|View full text |Cite
|
Sign up to set email alerts
|

D-SPACE4Cloud: A Design Tool for Big Data Applications

Abstract: The last years have seen a steep rise in data generation worldwide, with the development and widespread adoption of several software projects targeting the Big Data paradigm. Many companies currently engage in Big Data analytics as part of their core business activities, nonetheless there are no tools and techniques to support the design of the underlying hardware configuration backing such systems. In particular, the focus in this report is set on Cloud deployed clusters, which represent a cost-effective alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Therefore, in order to make the D-SPACE4Cloud usable, we focused on increasing the level of parallelism as much as possible. In [4] we have shown that, in the worst case, the relative error between performance prediction models and real applications execution can reach up to 32.97%, which is perfectly in line with the expected accuracy in the performance prediction field [8] while the average relative error is 14.13% overall.…”
Section: D-space4cloudsupporting
confidence: 75%
See 2 more Smart Citations
“…Therefore, in order to make the D-SPACE4Cloud usable, we focused on increasing the level of parallelism as much as possible. In [4] we have shown that, in the worst case, the relative error between performance prediction models and real applications execution can reach up to 32.97%, which is perfectly in line with the expected accuracy in the performance prediction field [8] while the average relative error is 14.13% overall.…”
Section: D-space4cloudsupporting
confidence: 75%
“…D-SPACE4Cloud [4] is the tool we used to evaluate the cost impact of privacy mechanisms implementation. D-SPACE4Cloud supports the capacity planning process of shared Hadoop Cloud clusters for MapReduce or Spark applications with deadline guarantees.…”
Section: D-space4cloudmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk tolerance knob introduced in ExoSphere allows easy and explicit characterization of portfolio risk. Transient server selection policies in earlier systems [20,36,43,45,49,57] do not have explicit support for managing revocation risk. This is because these systems have mostly targeted a single class of applications, and have server selection policies suited to that.…”
Section: Related Workmentioning
confidence: 99%
“…Our work is one of the first contributions facing the design time problem of rightsizing data-intensive Cloud systems adopting the Capacity Scheduler. In particular, it builds upon our previous research presented in [20] and provides a thorough description of D-SPACE4Cloud 1 , a software tool designed to help system administrators and operators in the capacity planning of shared Big Data clusters hosted in the Cloud to support both batch and interactive applications with deadline guarantees. With respect to previous releases, the tool now supports, besides classical MapReduce workloads, also Spark applications, which feature generic DAGs execution models.…”
Section: Introductionmentioning
confidence: 99%